Short Communication. Some wild bamboo clumps contain more than one genet - Franklin, Donald C; Kaneko, Shingo; Yamasaki, Nozomi; Isagi, Yuji (Australian journal of botany, 2008)
In clumping clonal plants, the often discrete nature of clumps may be enhanced by competition among genets. We examined the genetic composition of clumps of Bambusa arnhemica F.Muell., a bamboo from northern Australia, by analysis of microsatellites. Three of ten clumps were demonstrably multiclonal, containing a minimum of two, four and five genets, respectively. This raises intriguing questions about the development of clumps and suggests that intergenet competition may at times be overwhelmed by the benefits of coloniality in B. arnhemica.